Oral administration of a medium containing both D-aspartate-producing live bacteria and D-aspartate reduces rectal temperature in chicks. Issue 5 (3rd September 2017) - Do, P. H.; Tran, P. V.; Bahry, M. A.; Yang, H.; Han, G.; Tsuchiya, A.; Asami, Y.; Furuse, M.; Chowdhury, V. S.
ABSTRACT: 1. The aim of this study was to investigate the effects on the rectal temperature of young chicks of the oral administration of a medium that contained both live bacteria that produce D-aspartate (D-Asp) and D-Asp. 2. In Experiment 1, chicks were subjected to chronic oral administration of either the medium (containing live bacteria and 2.46 μmol D-Asp) or water from 7 to 14 d of age. Plasma-free amino acids as well as mitochondrial biogenic gene expression in the breast muscle were analysed. In Experiment 2, 7-d-old chicks were subjected to acute oral administration of the above medium or of an equimolar amount of D-Asp to examine their effect on changes in rectal temperature. In Experiment 3, after 1 week of chronic oral administration of the medium, 14-d-old chicks were exposed to either high ambient temperature (HT; 40 ± 1°C, 3 h) or control thermoneutral temperature (CT; 30 ± 1°C, 3 h) to monitor the changes in rectal temperature. 3. Chronic, but not acute, oral administration of the medium significantly reduced rectal temperature in chicks, and a chronic effect also appeared under HT conditions. 4. Chronic oral administration of the medium significantly reduced the mRNA abundance of the avian uncoupling protein (avUCP) in the breast muscle, but led to a significant increase in avian adenine nucleotide translocator (avANT) mRNA in the same muscle. 5. (a) These results indicate that the medium can reduce body temperature through the decline in avUCP mRNA expression in the breast muscle that may be involved in reduced mitochondrial proton leaks and heat production. (b) The increase in avANT further suggests a possible enhancement of adenosine triphosphate (ATP) synthesis.